Analisis Bibliometrik: Penggunaan Media Pembelajaran Macromedia Flash 8 di Sekolah Dasar (2019-2023) - Longso, Irmawati; Sukartiningsih, Wahyu; Istiq’faroh, Nurul (Journal of Comprehensive Science, 2024)
Bibliometric research is very important to provide readers with an understanding of research trends, compare authors or journals, and measure research contributions in scientific literature with the keyword "Macromedia Flash 8" on Scopus from 2019-2023. The methods used in this study are searching documents by keyword, using publish or perish, saving documents in the form of RIS files, and Using VOSviewer to display visualizations of bibliometric analysis. The results obtained from the VOSviewer analysis are that for analyzing scopus results there are 10 journals with details in 2019 and 2022, there are no scopus-indexed journals that match keywords, in 2020 there is an increase in research of scopus-indexed journals that match keywords, but in 2023 there is a decrease. Network Visualization has 347 items, 10 clusters, 10211 links, and 10724 total link strengths. The visualization Overlay shows that bright yellow has been researched while items that are opaque yellow such as class, mathematics, test, and others still lack research. The results of this study can provide space for other researchers to conduct further research.